Design, modeling and drafting of composite structures - Aronsson, Andreas (2005)
In January 2005 Volvo Aero Corporation (VAC) is about to enter an extensive EU-project regarding jet engine structures made of composite material. In conjunction with this project a number of students have been involved in a pre-study. As a masters thesis in mechanical design at Luleå university of technology a study of how to design, model and define composite components has been conducted. The overall aim is to find an effective way to work with components made out of composite material. A working method has been developed, evaluated and tested. The working method is a result of cooperation with Henrik Karlsson whose thesis is called “Evaluation of FE-software for mechanical analysis of composites”. The method is presented in this thesis together with explanations of the different stages in the following chapters. Different methods of modeling the internal structure of the composite have been tested. Furthermore studies of how different CAD tools can speed up and make the modelling of the internal material structure less time consuming has been performed. Standards of how to define parts made out of composite material on engineering drawings is also presented. Standards are used to embody generally accepted 'best practice' in composite design within several industries. To be able to visualize the different stages in the working method, a model of a ring-strut-ring configuration have been used. During the work different design guidelines have been collected and are presented in this thesis. Validerat; 20101217 (root)